Assessment of vulnerability to natural hazards a European perspective - Birkmann, Jörn; Kienberger, Stefan; Alexander, David (Elsevier, 2014)
Assessment of Vulnerability to Natural Hazards covers the vulnerability of human and environmental systems to climate change and eight natural hazards: earthquakes, floods, landslides, avalanches, forest fires, drought, coastal erosion, and heat waves. This book is an important contribution to the field, clarifying terms and investigating the nature of vulnerability to hazards in general and in various specific European contexts. In addition, this book helps improve understanding of vulnerability and gives thorough methodologies for investigating situations in which people and their environments are vulnerable to hazards. With case studies taken from across Europe, the underlying theoretical frame is transferrable to other geographical contexts, making the content relevant worldwide.--Provided by publisher.